Kritik Kekuasaan dalam Stand-Up Comedy: Analisis Wacana Kritis Pertunjukan "Komoidoumenoi" Pandji Pragiwaksono - Wafiq Azizah Ali; Vera Wijayanti Sutjipto (Jurnal Ilmu Komunikasi Dan Sosial Politik, 2026)
Stand-up comedy in Indonesia has evolved beyond entertainment to become a significant medium for political critique and social commentary. This study analyzes the discourse embedded in Pandji Pragiwaksono’s stand-up comedy show "Komoidoumenoi" (2020–2022), which explicitly references Aristophanes’ ancient Greek term for powerful figures made the subject of comic ridicule. Using Norman Fairclough’s three-dimensional Critical Discourse Analysis (CDA) framework, comprising text, discursive practice, and sociocultural practice, this research examines how Pandji constructs power critiques through linguistic choices, rhetorical strategies, and comedic framing. The findings reveal three dominant discursive strategies: (1) satire as a legitimating device for political criticism, (2) humor as a counter-hegemonic tool that subverts dominant power narratives, and (3) the strategic use of historical and cultural intertextuality to anchor contemporary political critique. This study argues that "Komoidoumenoi" functions not merely as entertainment but as a site of discursive resistance that challenges power structures while navigating the boundaries of public acceptability in post-Reformasi Indonesia.